Active Transportation, the Ultimate Low Carbon Way to Travel—A Review of International Research and Education - Allen, Heather; Nolmark, Henrik (Frontiers in Sustainable Cities, 2022)
Active transport is a relatively new term but one that has been gaining support over the past decade as an alternative to ‘on-motorized transport’ (NMT). Walking and cycling are considered to be the main transport modes within the active transport cluster. This paper summarizes the current state of international research and knowledge on active transport in urban and peri-urban areas in high-, middle- and low-income countries. It also explores current research gaps and potential ‘future looking’ research areas. The information was collected in early 2020 and is based on a rapid literature review, a 15-question Internet survey, semi-structured interviews, and a peer-review process with key actors and experts in active transport. Most respondents were professionally active in a broad range of areas directly or indirectly connected to the topic. A total of 112 cleaned responses were obtained from high-, middle- and low-income countries. The main findings show that there is a high level of scholarship in the subject, with a greater breadth and depth of research in high income countries. There has been an increase in attention since 1990. A key difference can be seen between cycling and walking and their positioning as transport modes. More papers on cycling are published in transport-related journals, while walking is better covered in health-related journals. Both are widely covered by work on road safety aspects. Based on the identified research gaps found in this review, suggestions are put forward for further possible research areas of interest on active transport in the post COVID recovery.